Olympic education as a method of humanistic elevation of students - Shcherbashyn, I. S. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to humanize the educational process through the introduction of older students of Olympic education. Material: the study involved 287 students of 10-11 class. Results: analyzed the level of awareness of Ukrainian pupils on Olympic themes, summarized the factors affecting the efficiency of the implementation of Olympic education in secondary schools. Found that a higher level of awareness of issues related to the development of the Olympic movement is seen in pupils who are in the rural areas - 57.5 % of respondents with respect to students in urban schools - 42.0 % of respondents. Conclusions: The effectiveness of the implementation of Olympic education is largely due to the construction of the educational process so that for a teenager, he acted as the satisfaction of his personal needs and interests, as a process of self-realization. Also important to have scientific support system of Olympic education; provide theoretical and methodological training of teachers.